Analisis Kelayakan Usaha Sego Babat Sapi’i Kabupaten Jember - Syafina Aulia Mulyonova; Gusti Nadya Ramadhanti Hariadhi; Lailatul Lutfia; Ungsa Lilis Purwanti; Dini Nuril Fadilah; M. Dadung Bimantoro (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to study and analyze the viability of the business at Sego Babat Sapi’I Jember with the attention of licensing aspects, aspects of production engineering, marketing, management, financial, as well as economic, social, and environmental aspects. The research method used is a type of qualitative descriptive method using primary data types through interviews with owners and employees. The results of the research explain that based on validity analysis on Sego Babat Sapi’i enterprise it can be concluded that the enterprise is worthy to be carried out. This is because even though the licensing aspect has not yet been licensed, other aspects support the business to be run well.